Methods to normalize surface electromyography in respiratory muscles: Is it similar between amyotrophic lateral sclerosis and healthy people? - Thiago Bezerra Wanderley E Lima; Jessica Danielle Medeiros da Fonseca; Ana Aline Marcelino da Silva; Rayane Grayce da Silva Vieira; Dayane Montemezzo; Matias Otto-Yáñez; Rodrigo Torres-Castro; Mário Emílio Teixeira Dourado Júnior; Vanessa Regiane Resqueti; Guilherme Augusto de Freitas Fregonezi (PLoS ONE)
The normalization process is important to determine the best approach for normalizing electromyographic signals from respiratory muscles in healthy subjects and those with ALS. The aim of this study is to compare different methods of normalizing the sEMG signal of respiratory muscles in both healthy subjects and those with Amyotrophic Lateral Sclerosis (ALS). This cross-sectional study was conducted in 67 subjects (50 healthy and 17 with ALS). The electrical activity of the sternocleidomastoid (SCM), scalene (ESC), diaphragm (DIA), parasternal (PS), external intercostal (EI), external oblique (EO), and rectus abdominal (RA) muscles were analyzed during maximal inspiratory pressure maneuvers (MIP), maximal nasal inspiratory pressure (SNIP), maximal expiratory pressure (MEP), and maximal voluntary isometric contraction of SCM and ESC (MVICSCM/ESC) and RA (MVICRA) using surface electromyography (sEMG). In the healthy group, inspiratory and expiratory muscles displayed higher electrical activity during MVICSCM/ESC and MIVCRA maneuvers, respectively (p<0.05). In the ALS group, inspiratory muscle activity was higher during the SNIP maneuver, while expiratory muscles showed higher activity during MVICRA (p<0.05). Based on the findings, it can be concluded that the MVIC resulted in greater inspiratory muscle activity, being the ideal method of normalization for inspiratory and expiratory muscles in healthy subjects. In ALS patients, the SNIP maneuver resulted in greater inspiratory muscle activity, while MVIC resulted in greater muscle activity in expiratory muscles.